Montenegro : Financial Sector Assessment Program-Banking Sector Stress Testing-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
The main objective of this technical note is to assess bank's balance sheet and profits, solvency stress test, and liquidity stress test. The financial system in Montenegro is dominated by the banking sector. By the end of 2014, 12 licensed banks operated in Montenegro, with total banking sector assets amounting to 3.1 billion euros or 88 percent of total financial system assets and 92 percent of GDP. The stress-testing exercise is aimed to test the banking system's resilience to extreme but plausible shocks. The stress test is a tool to assess the vulnerabilities of the banking system that may expose it to risks.